Visual diagnosis in utero: Prenatal diagnosis of Treacher-Collins syndrome using a 3D/4D ultrasonography - Sayo Kubo; Takashi Horinouchi; Masahiro Kinoshita; Toshiyuki Yoshizato; Yutaka Kozuma; Takaaki Shinagawa; Kimio Ushijima (Elsevier, 2019)
Objective: We present a case with prenatal diagnosis of Treacher-Collins syndrome in which micrognathia and other facial and ear abnormalities were described using a three- and four-dimensional (3D/4D) ultrasonography in utero. Case report: A 39-year-old Japanese pregnant woman was referred because of polyhydramnios at 29 weeks' gestation. Conventional ultrasonography showed a hypoplastic mandible on the sagittal section of fetal head. Continuous observation using a 3D ultrasonography additionally demonstrated bilateral downslanting palpebral fissures with symmetry and macrostomia as well as micrognathia. Both ears were microtia and no polydactyly or missing fingers were found. Conclusion: The advantage of the rendering mode of 3D images covering entire face including ears and limbs was enhanced by a continuous observation, so called 4D ultrasonography, under a condition of polyhydramnios, providing visual diagnosis in utero. Keywords: Prenatal diagnosis, Three-dimensional/four-dimensional ultrasonography, Treacher-Collins syndrome